Modulation of physical properties of organic cocrystals by amino acid chirality. (January 2021) - Ji, Wei; Xue, Bin; Bera, Santu; Guerin, Sarah; Shimon, Linda J.W.; Ma, Qing; Tofail, Syed A.M.; Thompson, Damien; Cao, Yi; Wang, Wei; Gazit, Ehud
Graphical abstract: Abstract: Amino acid chirality plays an important role in conveying directionality and specificity to their supramolecular organization. However, the impact of enantiopure and racemic amino acids on the favorable packing and macroscopic properties of organic cocrystals with nonchiral coformers is poorly understood. Herein, we performed a systematic study of the effect of chirality on the macroscopic properties of acetylated alanine (AcA) single crystals and cocrystals with a nonchiral photo-sensitive bipyridine derivative (BPE). Cocrystallization with BPE produced a marked morphology transition that improved the supramolecular chirality, thermal stability and mechanical strength of AcA crystals. The distinct supramolecular packing modes were analyzed by X-ray crystallography. The highest rigidity was observed for BPE/dl -AcA, while BPE/d -AcA and BPE/l -AcA crystals exhibited higher efficiency of photo-induced emission for fluorescent imprinting, as well as significantly higher piezoelectricity. This work provides a striking illustration that subtle differences in amino acid stereochemistry translate into tunable macroscopic properties of organic cocrystals for future applications in rigid solids, fluorescent imprinting, and energy harvesting.